Design and Development of an Integrated Online System Support for C/C++ Programming - Kokaew, Urachart (Science & Technology Asia, 2015)
One of the main problems for a lecturer of a computer programming course is the difficulty in providing quick feedback to every student’s coding solutions, especially in larger classes. To solve this problem, this study proposed an Integrated Online System Support for C/C++ programming language instruction. The designed system was based on the problem-solving model within the context of C/C++ programming and Gagné’s nine concepts. The system was developed as an online environment. The target group was the undergraduate students who were enrolled in the Introduction to Computer Programming course in the second semester for the academic year 2013 in the Department of Computer Science, Khon Kaen University, Khon Kaen, Thailand. We investigated the impact of the system on the students’ achievement and their satisfaction with this system. This area of the research was carried out using a learning achievement test and a questionnaire using the online environment. The data were analyzed using mean, standard deviation, an independent-samples T-test and a paired-samples T-test. The results of this research showed that the students’ post-test scores were significantly higher than their pre-test scores at .05 significance level. The questionnaire given at the very end of the experiment showed the satisfaction of participating students towards the system. Each question in the questionnaire showed students to be satisfied. Keywords: Design and development model; Web-based learning; Online learning.